Transcriptome and cytogenetic profiling analysis of matched in situ/invasive cutaneous squamous cell carcinomas from immunocompetent patients. Issue 3 (7th January 2019) - García‐Díez, Irene; Hernández‐Muñoz, Inmaculada; Hernández‐Ruiz, Eugenia; Nonell, Lara; Puigdecanet, Eulàlia; Bódalo‐Torruella, Marta; Andrades, Evelyn; Pujol, Ramon M.; Toll, Agustí
Abstract: Although most cutaneous squamous cell carcinomas (cSCCs) develop from actinic keratoses (AKs), the key events in this evolution remain unclear. We have combined the results of different genomic and expression array platforms on matched concomitant samples of sun‐exposed skin (SES), AK, and cSCC from 10 immunocompetent patients. Gene expression analysis and copy number alterations were assessed using GeneChip Human Gene 2.0 ST Array (Affymetrix, Santa Clara, CA) and CytoScan HD Cytogenetics Solution (Affymetrix) platforms, respectively. Integration of transcriptome and genome results was evaluated using the DR‐Integrator tool. Additional studies (qPCR, immunohistochemistry, and Western blot) were performed for selected genes. FOSL1 and BNC1 encode transcription factors whose expression was increased in cSCC in the expression array and the qPCR. By immunohistochemistry, FOSL1 showed an intense staining at the invasive front of cSCC samples and BNC1 expression varied from a nuclear (SES) to a cytoplasmic location (cSCC). Western blot analyses confirmed the enhancement of FOSL1 and BNC1. In addition, the smallest overlapping regions (SORIs) of genomic imbalance involving at least three of the samples were selected. One of the SORIs was a deletion in the p24.1 band of chromosome 3, shared by seven of the cSCCs. A strong correlation in the integration analysis was found for NEK10, a gene contained in the previously mentioned SORI. Loss of NEK10 expression in cSCC was confirmed by immunohistochemistry and Western blot analyses. In addition, functional studies in NEK10 depleted cells were performed. In conclusion, we identified FOSL1 and BNC1, which could act as tumor drivers, and NEK10, which could function as a tumor suppressor, to be differentially expressed during cSCC development.